Convergence of Precision Medicine and Public Health Into Precision Public Health: Toward a Big Data Perspective - Velmovitsky, Pedro Elkind; Bevilacqua, Tatiana; Alencar, Paulo; Cowan, Donald; Morita, Plinio Pelegrini (Frontiers in Public Health, 2021)
The field of precision medicine explores disease treatments by looking at genetic, socio-environmental and clinical factors, thus trying to provide a holistic view of a person’s health. Public health, on the other hand, is focused on improving the health of populations through preventive strategies and timely interventions. With recent advances in technology, we are able to collect, analyze and store for the first-time large volumes of real-time, diverse and continuous health data. Typically, the field of precision medicine deals with a huge amount of data from few individuals; public health, on the other hand, deals with limited data from a population. With the coming of Big Data, the fields of precision medicine and public health are converging into precision public health, the study of biological and genetic factors supported by large amounts of population data. In this paper, we explore through a comprehensive review the data types and use cases found in precision medicine and public health. We also discuss how these data types and use cases can converge towards precision public health, as well as challenges and opportunities provided by research and analyses of health data.